TECH SM4RT Tani enters partnership with key agriculture players, launches UrusTani - BOTS, team (The New Straits Times Press (M) Bhd., 2021)
KUALA LUMPUR: Agritech brand SM4RT Tani announced that the company has entered partnership with some key agriculture players to launch a farming management system called Urus Tani.